Max - Graham, Bob. (London : Walker Books, 2000)
Max, the young son of superheroes, is a late bloomer when it comes to flying, until he is inspired by the plight of falling baby bird.
Keywords: Flight -- Fiction; Flight -- Juvenile literature; Heroes -- Fiction; Heroes -- Juvenile literature